Psychometric Evidence of the INSEBULL Self-Report in Adolescents from Two Schools in the City of Cusco - Loaiza Dargent, Adriana Gabriela (2021)
The objective of the present study was to provide some psychometric evidences for the INSEBULL Self-Report, whose objective is to identify the measure to which students express a risk of getting involved in bullying. The sample consisted of 471 first to fourth high school students from a public and a private school in Cuzco (Peru). In the semantic validity study with 10 experts, it was found that all of the items, except the 34, had Aiken´s V values of .80 or more. Confirmatory factor analysis established a six-factor model. Cronbach´s alpha value for the total score was .873 and the factors of intimidation, victimization and expression of school fears had Cronbach’s alpha values greater than .80, while the factors of moral solution, lack of social integration and identification of the participants obtained values less than .60. Although significant differences between the total score of public and private schools was not found, we built separate norms for each of them, but at the same time, we advise to take care in using these norms, given the low internal consistency in the scores of several of the scales of this instrument.